2000
DOI: 10.4049/jimmunol.165.3.1513
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Receptor-Deficient Mice Have Impaired Neutrophil Recruitment in Response to PulmonaryPseudomonas aeruginosaInfection

Abstract: Leukocytes express both urokinase-type plasminogen activator (uPA) and the urokinase receptor (uPAR, CD87). Evidence in vitro has implicated uPAR as a modulator of β2 integrin function, particularly CR3 (CD11b/CD18, Mac-1). Pseudomonas aeruginosa infection has been demonstrated to recruit neutrophils to the pulmonary parenchyma by a β2 integrin-dependent mechanism. We demonstrate that mice deficient in uPAR (uPAR−/−) have profoundly diminished neutrophil recruitment in response to P. aeruginosa pneumonia compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
183
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(199 citation statements)
references
References 37 publications
11
183
1
Order By: Relevance
“…In addition, uPAR is capable of modulating cell adhesion by activating cells directly via a Gprotein-coupled receptor (8), by sequestering caveolin (9), and by affecting intracellular signaling events (10). In support of these in vitro studies, uPAR-deficient mice were found to respond poorly to Pseudomonas aeruginosa infection, because of impaired neutrophil infiltration and reduced monocyte adhesion (11). Clinically, up-regulation of uPAR expression within tumor cells was found to correlate inversely with the survival rate of breast cancer patients (3).…”
mentioning
confidence: 57%
“…In addition, uPAR is capable of modulating cell adhesion by activating cells directly via a Gprotein-coupled receptor (8), by sequestering caveolin (9), and by affecting intracellular signaling events (10). In support of these in vitro studies, uPAR-deficient mice were found to respond poorly to Pseudomonas aeruginosa infection, because of impaired neutrophil infiltration and reduced monocyte adhesion (11). Clinically, up-regulation of uPAR expression within tumor cells was found to correlate inversely with the survival rate of breast cancer patients (3).…”
mentioning
confidence: 57%
“…uPA also primes neutrophils for superoxide anion release (61), and uPAR expression is required for FMLP-dependent monocyte and granulocyte chemotaxis (45,46) and for neutrophil degranulation (62). Finally, uPA Ϫ/Ϫ and uPAR Ϫ/Ϫ mice show impaired neutrophil recruitment and susceptibility to bacterial infections (12)(13)(14). There is compelling evidence that mast cells and basophils are multifunctional effector cells in inflammation (63) and in host defense against bacteria, viruses and parasites (64).…”
Section: Discussionmentioning
confidence: 99%
“…Migration of immune cells to tissue lesions is impaired in uPA Ϫ/Ϫ and uPAR Ϫ/Ϫ mice, resulting in impairment of host defenses, bacterial spread, and death (12)(13)(14). Chemotaxis of inflammatory cells stimulated by uPA in vitro and in vivo requires binding to uPAR (15)(16)(17) and the existence of a transmembrane adapter (15,18).…”
mentioning
confidence: 99%
“…Such effects have been seen in a model of chemokine-induced leukocyte migration in uPA-deficient mice. 16 Gyetko et al 56 have observed that uPAR-deficient mice demonstrate impaired recruitment of leukocytes in response to infection and that such an altered response might affect tumor growth. Since leukocyte infiltration of xenotransplanted brain tumors is a very rare occurrence, and we have not observed any such infiltrates in our studies, such a mechanism is unlikely to be responsible for the slower tumor growth in our mice treated with these peptides.…”
Section: Discussionmentioning
confidence: 99%